IMPROVING THE STATE REGULATION OF MACHINE-BUILDING COMPLEX - I. G. Samigullin (Russian Journal of Economics and Law)
Objective: to define the main directions of the state regulation of machine-building complex and increasing its competitiveness. Methods: analysis; abstract-logical and systemic. Results: the general characteristic is given to the state regulation of machine-building complex development, the priority directions are determined of improving its components and high-technology aggregates; of increasing the added value of machine-building enterprises in Russia; of development competitive industry by stabilizing the market and forming the sources for innovative development. Scientific novelty: measures for state regulation of machine-building complex are proposed: 1) measures aimed at forming the market conditions of production in Russia; 2) measures aimed at the innovative development of machine-building complex; 3) measures of normative-legal regulation in this sphere. Practical value: possibility to implement the measures and main priority directions of state regulation of machine-building complex development at machine-building enterprises in Russia, which will promote its stability and increase competitive positions of the Russian machine-building industry.